Radio frequency thermal treatment as alternative insect pest control in storage - Krittigamas,N. (Chiang Mai University, 2015)
Pest control in farm crop production, storage and during marketing has been practiced in the tropics and sub-tropic conventionally with the chemical treatments. The demand for food safety for human health concerns, the green production for environmental friendly purposes, which are the alternatives to chemical treatments for insect pest control and management, become the research, policy, and practical challenges. Radio frequency (RF) treatment can be one of the appropriate technical measures taking into account the need for cost effectiveness for Thailand to be competitive in world agriculture. It was found that in the post-harvest management process, especially in rice preserved for packaging and exporting, post-harvest losses were usually found from infestation of insects during storage, which include rice weevil (Sitophilus oryzae L.), Angoumois grain moth (Sitotroga cerealella (Olivier)), rice moth (Corcyra cephalonica (Stainton)) and lesser grain borer (Rhyzopertha dominica (F.)). The efficacy of RF on controlling these storage insects showed the reaction of the insects depended on the insect species and their growth stage. After using RF (27.12 MHz) at 70°C for 150 sec of exposure time, this treatment completely controlled C. cephalonica in milled rice and 180 sec for controlling R. dominica in paddy rice. However the 100% mortality of S. oryzae, occurred at the lower temperature of 50°C for 15 min. The RF-tolerance stages of C. cephalonica and R. dominica were egg adult and larval stages, respectively. The effectiveness of RF on controlling stored insect would depend, without adverse effects on commodity of exposed agricultural products.